2009
DOI: 10.1128/aem.00062-09
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Burkholderia pseudomallei Strain Sensitivities to Chlorine Disinfection

Abstract: Burkholderia pseudomallei is a select agent and the causative agent of melioidosis. Variations in previously reported chlorine and monochloramine concentration time (Ct) values for disinfection of this organism make decisions regarding the appropriate levels of chlorine in water treatment systems difficult. This study identified the variation in Ct values for 2-, 3-, and 4-log 10 reductions of eight environmental and clinical isolates of B. pseudomallei in phosphate-buffered water. The greatest calculated Ct v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…Previously, both F. tularensis and Y. pestis dried onto non-porous surfaces were completely inactivated by vaporous hydrogen peroxide in chambers ranging in volume up to approximately 3,600 liters . Brucella suis and B. pseudomallei have been shown to be inactivated by freechlorine, monochloramine and ultraviolet light (O'Connell et al, 2009;Rose et al, 2007;Sagripanti et al, 2009); however, this study provides the first demonstration of inactivation by using vaporous hydrogen peroxide, especially on a large-scale.…”
Section: Discussionmentioning
confidence: 93%
“…Previously, both F. tularensis and Y. pestis dried onto non-porous surfaces were completely inactivated by vaporous hydrogen peroxide in chambers ranging in volume up to approximately 3,600 liters . Brucella suis and B. pseudomallei have been shown to be inactivated by freechlorine, monochloramine and ultraviolet light (O'Connell et al, 2009;Rose et al, 2007;Sagripanti et al, 2009); however, this study provides the first demonstration of inactivation by using vaporous hydrogen peroxide, especially on a large-scale.…”
Section: Discussionmentioning
confidence: 93%
“…For example, the Burkholderiales, which are known to contain strains resistant to antibiotics (27), were identified in high percentages in the postdisinfection samples in both systems. The sensitivity of Burkholderia to chlorine (28) and monochloramine (29) is known to vary considerably, with some isolates more tolerant than others. Previous research has revealed that cocultures of the pathogenic Burkholderia species Burkholderia pseudomallei with the ubiquitous freshwater amoeba Acanthamoeba astronyxis greatly enhances the survival of B. pseudomallei in the presence of monochloramine, with 100 times more monochloramine required to maintain disinfectant efficacy when the amoeba was present (29).…”
Section: Discussionmentioning
confidence: 99%
“…There appears to be much variation in tolerance to disinfectants within this species, though little is known about the resistance mechanism (Howard & Inglis 2003, 2005; O’Connell et al 2009). Some strains produce increased amounts of mucoid polysaccharide, which is readily observed in their colonial morphology, and has been reported to affect resistance to UV light, but was not directly correlated to FAC resistance (Howard & Inglis 2005).…”
Section: Chlorinementioning
confidence: 99%
“…One study conducted with Australian isolates found some cells in a test suspension survived 1,000 mg L −1 FAC, using a broth-based most probable number (MPN) culture method (Howard & Inglis 2003). In contrast, using the same MPN culture method as well as a standard plate count culture method, O’Connell et al (2009) tested 11 strains of various origins and morphologies (but not the same Australian isolates mentioned previously) and found that all strains were inactivated within 10 minutes with a FAC concentration of 1 mg L −1 (Table 2). These findings suggest that a wide range of susceptibility exists within the species.…”
Section: Chlorinementioning
confidence: 99%